2014
DOI: 10.1016/j.toxrep.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro steatosis hepatic cell model to compare the lipid-lowering effects of pomegranate peel polyphenols with several other plant polyphenols as well as its related cholesterol efflux mechanisms

Abstract: This study was aimed to compare the relative activities of the purified pomegranate peels polyphenols (PPPs) with some other plant polyphenols including punicalagin, ellagic acid, gallic acid, phlorizin, and epigallocatechin gallate (EGCG) on the lipid metabolism regulation, and the cholesterol efflux mechanisms of PPPs and punicalagin were also investigated. In this paper, a convenient and accurate in vitro HL7702 steatosis hepatic cell model was applied to evaluate the lipid-lowering effects of the tested po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The mechanism underlying the ellagic acid effects in these studies was related to promotion of hepatic fatty acid oxidation by upregulating CPT‐1 and PPARα and to maintenance of cholesterol homeostasis by increasing hepatic expression of ApoA1 and LDL receptor. More precisely, our group showed that pomegranate peel polyphenols exhibit the most significant lipid‐lowering capacity among other tested plant polyphenols including punicalagin, ellagic acid, gallic acid, phlorizin, and epigallocatechin gallate in hepatocyte‐derived HL7702 cells and that punicalagin displayed the strongest lipid‐lowering effects among all the tested components of pomegranate peel polyphenols …”
Section: Effects Of Pomegranate On Nafldmentioning
confidence: 86%
See 1 more Smart Citation
“…The mechanism underlying the ellagic acid effects in these studies was related to promotion of hepatic fatty acid oxidation by upregulating CPT‐1 and PPARα and to maintenance of cholesterol homeostasis by increasing hepatic expression of ApoA1 and LDL receptor. More precisely, our group showed that pomegranate peel polyphenols exhibit the most significant lipid‐lowering capacity among other tested plant polyphenols including punicalagin, ellagic acid, gallic acid, phlorizin, and epigallocatechin gallate in hepatocyte‐derived HL7702 cells and that punicalagin displayed the strongest lipid‐lowering effects among all the tested components of pomegranate peel polyphenols …”
Section: Effects Of Pomegranate On Nafldmentioning
confidence: 86%
“…Liver X receptor alpha (LXRα) and its target gene—ATP‐binding cassette transporter A1 (ABCA1)—are able to stimulate RCT via elevating HDL‐C . Pomegranate peel extracts were also found to ameliorate NAFLD development by increasing the mRNA levels of LXLα and ABCA1 in HL7702 cells . Cholesterol 7α hydroxylase (CYP7A1) is the first rate‐limiting enzyme in the transformation of cholesterol into bile acids .…”
Section: Effects Of Pomegranate On Nafldmentioning
confidence: 99%
“…SMMC-7721 and HL-7702 cells were also incubated in 50% FBS [32] for 24 h, 48 h or 72 h, and the cell samples were then harvested for further analysis. At least three replicates of each experiment were performed.…”
Section: Animalsmentioning
confidence: 99%
“…Thus, ellagic acid promotes cholesterol removal by regulating LXR/PPAR-ABCA1 pathway (Zhao S. et al, 2016). Pomegranate peel extract and punicalgin up-regulate mRNA expression of LXRa and ABCA1 (Zhao et al, 2014). Ellagic acid and punicalagin cause anti-oxidant effect by reducing ROS level produced by mitochondria (Hwang et al, 2010;Zou et al, 2014).…”
Section: Possible Anti-atherosclerotic Mechanisms Of Medicinal Plantsmentioning
confidence: 99%